An Implementation Of IPC Using Direct Thread Switching (International Journal of Engineering and Computer Science, 2017)
Microkernel approach restructures the existing operating system by removing all nonessentialcomponents from the kernel and implementing them as user-level programs. The main function of themicrokernel is to provide a communication facility, such as inter-process communication (IPC), between theclient program and the various services that are also running in user space. Since IPC occurs very often inmicrokernel, the performance of IPC highly affects the overall performance of the system. The performance ofIPC decreases tremendously when there are many threads in ready state because many threads need to executebefore IPC receiver thread begins. One of solutions to this problem is direct thread switching, which schedulesthe receiver thread immediately after the sender thread send a data. In this paper, we implemented synchronousIPC for microkernel and adopted direct thread switching to improve IPC performance. Carrying out extensiveperformance measurement studies, we showed that direct thread switching enormously improves theperformance of IPC.